Evaluation of physicochemical properties of modified algae protein adhesives - Borgen, Kelly (Kansas State University, 2012)
Algae proteins have similar amino acid compositions as conventional plant proteins, and are comparatively richer in the essential amino acids. Algae protein has the potential to be used in the development of a wide variety of products, including foods, animal feeds, bioplastics, and adhesives. The utilization of algae protein for value-added products would increase the economic feasibility of algae biodiesel. This research evaluated the adhesion, rheological, morphological, and thermal properties of adhesives made from algae protein extracted from Cladophora sp. and modified with either sodium hydroxide (pH 9, 10, 11) or sodium dodecyl sulfate (SDS, 0.5, 1, and 3%). Both alkali-modified and SDS-modified algae protein adhesives displayed improved dry shear strength compared to unmodified algae protein. However, only 3% SDS-modified algae protein significantly improved the water resistance as shown in wet and soak shear strength tests. Thermal analysis using differential scanning calorimetry showed that SDS modification caused complete denaturation of the algae protein. SDS modification also increased the viscosity of the adhesive and created rougher particle surface texture. These data suggest that SDS modification can effectively increase shear strength and water resistance of algae protein adhesives caused by protein denaturation and protein structure change.
Keywords: Modified algae protein adhesives; Shear strength; Sodium dodecyl sulfate; Rheology; Differential scanning calorimetry; Scanning electron microscopy; Engineering (0537); Engineering, Agricultural (0539); Sustainability (0640)